2011
DOI: 10.1159/000329094
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Neonatal Autopsy

Abstract: Background and Objective: Neonatal autopsy rates were in decline internationally at the end of the last century. Our objective was to assess the current value of neonatal autopsy in providing additional information to families and healthcare professionals. Methods: We conducted a review of neonatal autopsies performed in a tertiary perinatal centre over an 11-year period. Primary outcomes measured were the annual neonatal autopsy rates and concordance rates between clinical and autopsy diagnoses of the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…3,4 Existe amplio consenso acerca de los aportes de la autopsia neonatal en la confirmación de los diagnósticos clínicos, en identificar afecciones y malformaciones congénitas [7][8][9] en su contribución a la educación médica, 10 así como también sobre su valor desde el punto de vista médico-legal.…”
Section: Discussionunclassified
“…3,4 Existe amplio consenso acerca de los aportes de la autopsia neonatal en la confirmación de los diagnósticos clínicos, en identificar afecciones y malformaciones congénitas [7][8][9] en su contribución a la educación médica, 10 así como también sobre su valor desde el punto de vista médico-legal.…”
Section: Discussionunclassified
“…The causes of the deaths were usually based on clinical, rather than pathologist reports, as there has been a general decline in neonatal and paediatric autopsy rates over the last 20 years. [87][88][89] It is not surprising therefore that all of the trial investigators who completed the section of the questionnaire about post-mortem data reported that these data were not specifically collected as part of the trial protocol. Most PIC investigators (66.7%) reported that post-mortem data were unnecessary compared with less than half (47.8%) of NIC investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem examination can provide families with a cause of death following fetal demise or death of a neonate or infant, with information obtained from the autopsy contributing to the management of future pregnancies in up to 40% of cases. Autopsy also provides tissue for research into congenital disease, assists in comprehensive audit of obstetric practice, and offers a method of infectious disease surveillance in low‐ or middle‐income countries.…”
Section: Introductionmentioning
confidence: 99%